The Influence Of E-Service Quality And Shopping Experience On Repurchase Intentions Mediated By Consumer Trust In Shopee Application Users In Padang City - Dinda Murty Kencana; Whyosi Septrizola (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The purpose of this study is to examine: (1) e-service grade on shopee users' repurchase intention in padang city (2) The impact of shopping expertise in shopee consumers' repurchase intention in padang city in padang city (3) the influence on the quality of e-services on trust of shopee consumers' in padang city (4) influence of shopping experience on trust of shopee users in padang city (5) influence of trust on shopee users' repurchase intention in Padang City (6) ) e-service quality on shopee users' repurchase intention in Padang City with trust serving as a moderating factor (7) the impact of shopping expertise in shopee users' rebuy intentions in padang city with trust as a mediating variable, the type of this research is quantitative descriptive research, the number of samples in this research is 160 respondents using purposive sampling techniques, the data analysis method uses SEM analysis using the Smart PLS 4 application. The results of the research are (1) In Padang City, customers' intention to repurchase products is significantly influenced by the quality of their e-services. (2) Shopee users' intentions to make additional purchases in Padang City are significantly influenced by their shopping experiences. (3) In the city of Padang, customers' trust in Shopee is greatly impacted by the quality of their e-services. (4) In the city of Padang, shoppers' trust in Shopee is greatly impacted by their shopping experiences. (5) Shopee users in Padang are highly influenced by trust when it comes to their intention to make another purchase. (6) Shopee users' intentions to repurchase are significantly influenced by the quality of their e-services, with trust acting as a mediating factor in Padang City. (7) There is a big impact. Shopee users' intentions to repurchase in Padang City are influenced by their shopping experiences, with trust acting as a mediating factor.